Meninjau Ulang Perspektif Hidup Berkelimpahan Dan Hidup Berkekurangan Dalam Konteks Doa Orang Kristen - Timbuleng, Nontje Mery (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2023)
This article aims to review the perspective of living in abundance and living in need in the context of Christian prayer, focusing on the role of prayer in shaping people's spiritual attitudes and understanding of these two circumstances. The problem in the practice of the Christian faith, many people feel confused between living a life of abundance associated with material blessings and living a life of deprivation which is often considered a test. The tension between these two perspectives can affect the way people pray and interact with God and others. This research uses a qualitative approach method with theological analysis of biblical texts, spiritual literature, and in-depth interviews with faith practitioners. Thus, this article collects various views and experiences of Christians regarding prayer in the context of abundance and deprivation. The result to be achieved is that prayer functions as a bridge that connects the people with God in various circumstances. The end of this article is a conclusion that confirms the results of the research achieved.